2013
DOI: 10.1016/j.preteyeres.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Optic neuritis in neuromyelitis optica

Abstract: Neuromyelitis optica (NMO) is an autoimmune demyelinating disease associated with recurrent episodes of optic neuritis and transverse myelitis, often resulting in permanent blindness and/or paralysis. The discovery of autoantibodies (AQP4-IgG) that target aquaporin-4 (AQP4) has accelerated our understanding of the cellular mechanisms driving NMO pathogenesis. AQP4 is a bidirectional water channel expressed on the plasma membranes of astrocytes, retinal Müller cells, skeletal muscle, and some epithelial cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 169 publications
(195 reference statements)
3
46
1
2
Order By: Relevance
“…First, the long, thin cylindrical dimension of the optic nerves with the cul-de-sac anatomy of the subarachnoid space may cause unique cerebrospinal fluid (CSF) dynamics, including restricted diffusion of proinflammatory elements (eg, AQP4 antibodies), retained inflammation, and limited clearance of myelin and axonal debris, followed by enhanced NMOsd lesion formation. 28,29 We revealed prominent pathological meningeal thickening with inflammation (see Fig 4) and radiologically abnormal enhancement of the OPN pattern in NMOsd (see Fig 1). Inflammatory processes may contribute to the closing of the arachnoid apertures that drain CSF into the meningeal lymphatics, thus adding to CSF compartmentalization.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…First, the long, thin cylindrical dimension of the optic nerves with the cul-de-sac anatomy of the subarachnoid space may cause unique cerebrospinal fluid (CSF) dynamics, including restricted diffusion of proinflammatory elements (eg, AQP4 antibodies), retained inflammation, and limited clearance of myelin and axonal debris, followed by enhanced NMOsd lesion formation. 28,29 We revealed prominent pathological meningeal thickening with inflammation (see Fig 4) and radiologically abnormal enhancement of the OPN pattern in NMOsd (see Fig 1). Inflammatory processes may contribute to the closing of the arachnoid apertures that drain CSF into the meningeal lymphatics, thus adding to CSF compartmentalization.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, abundant large orthogonal arrays of particles (OAPs) in astrocytic endfeet of the optic nerves enhance binding of AQP4 antibodies and complement-dependent astrocyte damage. 28 These unique structures of the optic nerves may promote typical NMOsd lesions that show a pattern-specific loss of AQP4 with complement activation. Importantly, we demonstrated that severe and widespread neurodegeneration with aberrant accumulation of degenerative mitochondria and TRPM4 channels was evident in the optic nerves in NMOsd.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromyelitis optica (NMO) and multiple sclerosis (MS) are autoimmune demyelination diseases that mainly affect the central nervous system (CNS)1 and optic neuritis (ON) is the most common initial manifestation of NMO and MS. Isolated ON with aquaporin-4 antibody (AQP4-Ab) seropositivity (AQP4-Ab+/ON) has a high risk of converting to definite NMO in clinical practice; therefore, AQP4-Ab+/ON is presumed to have a similar pathogenesis as definite NMO such that when AQP4-Ab binds to its receptors it causes complement deposition, which results in astrocyte injury and secondary axonal demyelination from oligodendrocyte injury 2 3. Therefore, AQP4-Ab+/ON is considered an early or limited type of NMO and has been named an NMO spectrum disorder (NMOSD).…”
Section: Introductionmentioning
confidence: 99%
“…NMO is much less common than MS (perhaps 1% of optic neuritis is due to NMO)3 but their pathophysiology is significantly different 21. Unlike MS, NMO requires immunosuppressive therapy.…”
Section: Mimicsmentioning
confidence: 99%